Experimental Investigation on the Optical and Stability of Aqueous Ethylene Glycol/Mxene as a Promising Nanofluid for Solar Energy Harvesting - K., Kadirgama; L., Samylingam; Aslfattahi, Navid; M., Samykano; D., Ramasamy; R., Saidur (IOP Publishing, 2021)
In this research work, emerged nanomaterial (MXene) and Ethylene Glycol (EG) as base fluid is used to formulate a homogenous mixture of nanofluid with promising optical properties. Amphiphilic structure of ethylene glycol allows the dispersion of water and MXene nanoflakes appropriately. The studied nanofluids are prepared with a mixture of 70 % of EG and 30% of deionized water. The prepared aqueous EG is mixed with Ti3C2 nanoflakes with three different loading concentrations of 0.02, 0.05, and 0.1 wt.%. The Fourier Transform Infrared spectrum (FTIR) of the aqueous EG/MXene nanofluids is measured using a Perkin Elmer Spectrum Two-Universal ATR. Particle analyzer is used to measure the stability of the prepared nanofluids. The experimentally achieved data represents the highest stability with mean zeta potential value of -92.6 mV for aqueous EG/MXene with a loading concentration of 0.02 wt.%. Optical absorbance measurements are performed using Ultraviolet-visible (UV-Vis) spectroscopy. Perkin Elmer Lambda 750 is used to acquire spectra. The result of the observation indicates that the solution of nanofluid with a loading concentration of 0.1 wt. % of Ti3C2 exhibits the highest peak magnitude of light absorbance among the rest of the three samples. This is because of the more mass concentration value of that nanofluid solution, which is proportional to light absorption. Due to the hydrophilic nature of the utilized nanomaterial and base fluid, there is an excellent probability for them to form a potential homogenous mixture of nanofluid, which might accomplish high optical performance in terms of applying at the solar system.